2009
DOI: 10.1016/j.ijid.2008.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of isolation of various subtypes and antimicrobial resistance of Shigella from urban slums of Karachi, Pakistan

Abstract: Concurrent circulation of multiple strains with high resistance is worrying and mandates surveillance at the national level to facilitate the control of shigellosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 26 publications
5
34
2
Order By: Relevance
“…The increasing trend of S. sonnei from 35% (50/144) in 2010 to 41% (63/154) in 2012 was also observed in another study conducted in rural areas of Bangladesh (Talukder et al ., unpublished data). Similar trend was noticed in many developed and industrialized countries [27] including India [28] and Pakistan [29]. The reasons for this shifting trend have been suggested to be an improvement of overall nutritional status [8], [30], socioeconomic status [31], sanitation condition [32], and a reduction of the chances of cross immunity imparted by Plesiomonas shigelloides [33].…”
Section: Discussionsupporting
confidence: 53%
“…The increasing trend of S. sonnei from 35% (50/144) in 2010 to 41% (63/154) in 2012 was also observed in another study conducted in rural areas of Bangladesh (Talukder et al ., unpublished data). Similar trend was noticed in many developed and industrialized countries [27] including India [28] and Pakistan [29]. The reasons for this shifting trend have been suggested to be an improvement of overall nutritional status [8], [30], socioeconomic status [31], sanitation condition [32], and a reduction of the chances of cross immunity imparted by Plesiomonas shigelloides [33].…”
Section: Discussionsupporting
confidence: 53%
“…In uni-variate analysis, we further observed that the infection with Shigella sonnei was significantly associated with encephalopathy, although many previous studies have reported no association between the infecting species of Shigella with encephalopathy [10,11,44]. Our observed association might represent the rising trend and increasing virulence of Shigella sonnei [1,45,46]. We also observed Shigella sonnei as the second most common species of Shigella among our study population [1], which might represent the improvement of overall nutritional and socioeconomic status.…”
Section: Discussionmentioning
confidence: 49%
“…Shigella flexneri was isolated predominately from Ethiopia [7, 8, 14], Kenya [9, 13], Eritrea [11], Ghana [12], Pakistan [16], Iran [17, 22], China [19, 27], Nepal [23, 28], India [29] and Brazil [31] (Table 1). S. sonnei was also isolated predominately from Ethiopia [13], Thailand [18], Vietnam [24] and Iran [25, 26], Chile [21] and Trinidad [30].…”
Section: Resultsmentioning
confidence: 99%